2015
DOI: 10.1136/bmjopen-2014-006048
|View full text |Cite
|
Sign up to set email alerts
|

HFE gene mutation and oxidative damage biomarkers in patients with myelodysplastic syndromes and its relation to transfusional iron overload: an observational cross-sectional study

Abstract: ObjectiveA relation between transfusional IOL (iron overload), HFE status and oxidative damage was evaluated.Design, setting and participantsAn observational cross-sectional study involving 87 healthy individuals and 78 patients with myelodysplastic syndromes (MDS) with and without IOL, seen at University Hospital of the Federal University of Ceará, Brazil, between May 2010 and September 2011.MethodsIOL was defined using repeated measures of serum ferritin ≥1000 ng/mL. Variations in the HFE gene were investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…The frequency of HFE SNVs in our patient cohort was as previously reported in the literature (Marchall et al , ; De Souza et al , ; Lee et al , ). In particular, the frequency of the H63D variant was 22·7% (10 out of 44 patients), whereas it was 4·5% (2 out of 44 patients) for both S65C and C282Y SNVs.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…The frequency of HFE SNVs in our patient cohort was as previously reported in the literature (Marchall et al , ; De Souza et al , ; Lee et al , ). In particular, the frequency of the H63D variant was 22·7% (10 out of 44 patients), whereas it was 4·5% (2 out of 44 patients) for both S65C and C282Y SNVs.…”
supporting
confidence: 87%
“…The authors reported that neither patients' characteristics (including baseline and follow-up ferritin concentrations), nor mutations in any of the specific genes frequently mutated in myeloid malignancies showed significant associations with the occurrence of HI during ICT. We would like to point out that haemochromatosis (HFE) gene mutations, which affect significant proportion of MDS patients and increase the risk of iron accumulation in this context (De Souza et al, 2015;Lucijanic et al, 2016), were not assessed by Fabiani et al (2019).…”
Section: Could Haemochromatosis (Hfe) Gene Mutations Affect Response mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on stratification to clinical manifestations, the isolated RAOU was negatively associated with HLA-A1 with a difference close to significance (12 [14.81%] vs. 32 [26.02%] in HCs; p = 0.06). Furthermore, patients with mucocutaneous features had a higher frequency of HLA-B51 (14, 24.14%) than patients without mucocutaneous involvement (11,11.37%). Considering HFE mutations, patients with isolated RAOU had a higher frequency of H63D when compared with other subgroups, especially after limiting the comparison to 27 patients of at least 5 years of followup.…”
mentioning
confidence: 99%
“…The HFE mutation is encountered in hereditary hemochromatosis [6] . It is also implicated in other diseases, such as neoplasia [8][9][10] and myelodysplastic syndromes [11] . Its association with RAOU or BD has not yet been described.…”
Section: Introductionmentioning
confidence: 99%